Comparative study on rhizosphere colonization by some mutant and wild isolates of Trichoderma species - and SITANSU PAN, AYON ROY (Indian Phytopathology, 2004)
The ability to colonize groundnut rhizosphere by some g ray induced mutants and wild isolates of Trichoderma harizanum and Trichoderma virens was determined upto 70 DAS. All isolates multiplied in groundnut rhizosphere and the multiplication was several folds higher in sterilized soil over natural one. Variation in rhizosphere population in non-sterilized soil was detected only after 28 days whereas significant variation in population dynamics in sterilized soil was recorded at very early stage (14 DAS) among the mutants. A gradual decline in rhizosphere population was recorded upto 42 DAS and there after an inconsistent fluctuation in population was noticed upto 70 days for most of the isolates. Considering the overall performance, mutant isolates 50Th3VI, 150Th3I, 125Th4I, 75Tv1VI, 150Tv1II and 75Tv3I appeared greater rhizosphere competent over their wild counterparts.